A combined mesowear analysis of Mexican Bison antiquus shows a generalist diet with geographical variation. (19th June 2018) - Díaz-Sibaja, Roberto; Jiménez-Hidalgo, Eduardo; Ponce-Saavedra, Javier; García-Zepeda, María Luisa
Abstract: Bison antiquus Leidy, 1852 was one of the largest and most widely distributed megafaunal species during the Late Pleistocene in North America, giving rise to the modern plains bison in the middle Holocene. Despite the importance of the ancient bison, little is known about its feeding ecology. We employed a combination of extended mesowear, and mesowear III to infer the dietary preference and habitat use of three Mexican samples of B. antiquus . These included two northern samples—La Piedad-Santa Ana and La Cinta-Portalitos—from the Transmexican Volcanic Belt morphotectonic Province, as well as one southern sample—Viko Vijin—from the Sierra Madre del Sur morphotectonic province. We found that the northern Mexican samples were primarily nonstrict grazers, whereas the southern sample displays a pattern consistent with mixed feeding habits. This suggests variability among the diets of the bison from these samples, caused by different paleoenvironments. This evidence complements the paleoenvironmental reconstructions in the studied localities; for the northern samples, open prairies composed of patches of woodland or shrubland and, for the southern locality, a fluvial floodplain with short-lived vegetation. In both scenarios, grasses (Poaceae) were nondominant. The dietary habits of our samples of ancient bison in Mexico are the southernmost dietary inference for the species in North America and expand our knowledge of the dietary habits of B. antiquus during the Late Pleistocene.